2015
DOI: 10.1002/adhm.201500623
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Starch/Polycaprolactone Aligned Magnetic Responsive Scaffolds for Tendon Regeneration

Abstract: The application of magnetic nanoparticles (MNPs) in tissue engineering (TE) approaches opens several new research possibilities in this field, enabling a new generation of multifunctional constructs for tissue regeneration. This study describes the development of sophisticated magnetic polymer scaffolds with aligned structural features aimed at applications in tendon tissue engineering (TTE). Tissue engineering magnetic scaffolds are prepared by incorporating iron oxide MNPs into a 3D structure of aligned SPCL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
58
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 54 publications
1
58
1
Order By: Relevance
“…3D magnetic TE systems are typically achieved by the direct incorporation of MNPs into a 3D scaffold matrix or by previous association with seeded cells through cell labeling or internalization. 70 This renders magnetic responsiveness to the tissue substitute with the potential to be remotely controlled and tuned by the actuation of an external magnetic field.…”
Section: Magnetic Tissue Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…3D magnetic TE systems are typically achieved by the direct incorporation of MNPs into a 3D scaffold matrix or by previous association with seeded cells through cell labeling or internalization. 70 This renders magnetic responsiveness to the tissue substitute with the potential to be remotely controlled and tuned by the actuation of an external magnetic field.…”
Section: Magnetic Tissue Engineeringmentioning
confidence: 99%
“…70 These magnetic scaffolds aimed at tendon regeneration, and they were shown to assist in the tenogenic differentiation of human adipose-derived stem cells under magneto-stimulation conditions. The magnetic scaffolds also evidenced good biocompatibility and integration within the surrounding tissues on implantation in an ectopic rat model.…”
Section: Magnetic Tissue Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue engineering magnetic scaffolds were synthesized by incorporating iron oxide magnetic nanoparticles (MNPs) into a 3D structure of aligned starch and polycaprolactone (SPCL) fibers fabricated by rapid prototyping (RP) technology. The authors concluded that the effect of the magnetic aligned scaffolds structure combined with magnetic stimulation, has a significant potential to impact the field of TTE towards the development of more efficient regeneration therapies [56].…”
Section: Materials Available For Am For Medical Applicationsmentioning
confidence: 99%
“…[28], [82], [83], [84] MNPs can be integrated within 3D scaffolds directly or by previous association with (stem) cells ( Figure 1.3E). [85] After incorporation, the application of an external magnetic field may induce scaffold structure deformation. The matrix structure and properties will relate to their application and on the fabrication The strategies to produce magnetic spheres are the encapsulation of MPs in a biodegradable polymeric matrix that usually rely on either i) uniformly disperse MPs within the polymeric matrix; ii) induce the formation of a MPs core within the sphere; or iii) the fabrication of spheres with a polymeric matrix core coated with MPs ( Figure 1.3 C).…”
mentioning
confidence: 99%